Exponentiating derivations of quasi ∗-algebras: possible approaches and applications. (27th October 2005) - Bagarello, F.; Inoue, A.; Trapani, C.
Abstract : The problem of exponentiating derivations of quasi ∗ -algebras is considered in view of applying it to the determination of the time evolution of a physical system. The particular case where observables constitute a properC Q ∗ -algebra is analyzed.